Jaring Pengaman Sosial Bidang Pendidikan sebagai Upaya Pengentasan Kemiskinan di Kabupaten Sleman - Niken Lestari (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2021)
The number of poor people in Sleman Regency for three consecutive years in 2018 is 92 thousandpeople, in 2019 it is 90 thousand people, and in 2020 it is 100 thousand people. In 2019 itdecreased from the previous year, but in 2020 it experienced a significant increase, namelyaround 10 thousand people. The poverty line for the last 3 consecutive years, in 2018 thepercentage of poor people was 7.65%, in 2019 the percentage was 7.41%, and in 2020 it increasedto 8.12%. Social safety net, hereinafter abbreviated as JPS, is unplanned social assistance in theform of money given to residents of Sleman Regency with socio-economic status as poor and/orvulnerable to poverty and neglect in Sleman Regency. The scope of the Social Safety Net coversthree areas, namely the health, education and social sectors. The social safety net in SlemanRegency from 2017 to 2021 is running well. Every year, the budget provided for JPS is IDR 10billion. In the education sector, there were the most submissions compared to other fields fromJanuary 2019 to July 2020. This proves that the social safety net in the education sector is analternative for people in the Sleman Regency area who experience difficulties in meetingeducation costs. Submission of the JPS budget in the education sector can be used to pay offoutstanding tuition fees, building fees, and pay off fees to be able to take diplomas. The hope isthat with better education, people who experience economic difficulties can organize their lives sothat they can improve their family's economy to be even better